Penguatan pengetahuan ibu hamil dalam monitoring kadar Hb - Fitri Suciana; Arlina Dhian Sulistyowati; Devi Permatasari; Fitriana Noor Khayati (Universitas Muhammadiyah Klaten, 2024)
The first trimester of pregnancy is the time of formation of important organs of the fetus including the central nervous system and fetal heart, starting the formation of eye organs, arms and legs. In the second trimester, the fetus begins to develop external genitalia, thicker skin, opaque with fine hair (lanugo). The formation and development of important organs of the fetus requires adequate nutrients from the mother through the placenta. Hemoglobin has a role in the transportation of nutrients and oxygen in the process of fetal development. Self-care of pregnant women during antenatal to increase Hb levels is needed in the prevention of anemia in pregnant women including knowledge management, Self-care of pregnant women during antenatal to increase Hb levels is needed in the prevention of anemia in pregnant women including knowledge management, The purpose of this community service is to introduce the prevention of anemia and the impact of anemia on pregnant women, so that pregnant women can take preventive action. The steps needed in preventing anemia include education and Hb testing for pregnant women.